2015
DOI: 10.1097/ijg.0000000000000143
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of Spectral-Domain Optical Coherence Tomography RNFL Map for Glaucomatous and Fellow Normal Eyes in Unilateral Glaucoma

Abstract: The test-retest variabilities of the Cirrus HD-OCT RNFL thickness map of the glaucomatous eyes were lower than those of the fellow normal eyes, especially in areas of high diagnostic importance. Moreover, variability was positively correlated with the baseline RNFL thicknesses. Therefore, adjusting the tolerance limits on the basis of the baseline RNFL thickness values might help improve the ability to recognize progression. Further prospective studies on this issue are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 32 publications
0
6
1
Order By: Relevance
“…In adults, the effect of disease severity in glaucoma on reproducibility has been contradictory. Studies using Cirrus OCT on normal and glaucoma eyes have shown both similar [ 23 ] and worse [ 24 ] reproducibility in the affected eyes. Whether, the intra-and inter variations are affected in children with optic nerve diseases has to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…In adults, the effect of disease severity in glaucoma on reproducibility has been contradictory. Studies using Cirrus OCT on normal and glaucoma eyes have shown both similar [ 23 ] and worse [ 24 ] reproducibility in the affected eyes. Whether, the intra-and inter variations are affected in children with optic nerve diseases has to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal thickness of the macula and the RNFL in the optic disc is associated with numerous ocular disease states. Thinning of the RNFL is a characteristic trait of glaucoma 12 , 13 and changes in RNFL thickness are evident in patients with myopia. 14 , 15 Furthermore, RNFL thickness is increased in individuals with amblyopia, 16 and the thickness of the GCL in the macula is increased in patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Optical coherence tomography (OCT) is a high-resolution cross-sectional imaging technique that allows for in vivo quantification of the retinal nerve fiber layer (RNFL) and the optic disc features, thereby enabling determination of both the presence and progression of glaucomatous structural damage [ 13 , 14 ]. The measurement of RNFL thickness differences in follow-up visits is very important, especially for detecting the progression of glaucoma.…”
Section: Introductionmentioning
confidence: 99%